The Legal Logic of the Collapse on Non-Retroactive Doctrine in the Constitutional Court Decision - Muda, Iskandar (Constitutional Review, 2017)
The non-retroactive doctrine as a legal principle did not apply retroactively. In legal system of Indonesian; Article 28I paragraph (1) of 1945 Constitution determines that a human right can not be prosecuted based on retroactive law as well as rights that can not be reduced under any circumstances. Similarly Article 58 of Law No. 24 Year 2003 concerning Constitutional Court determines that a Law is being reviewed by the Constitutional Court is still applied, before there is decision stated that the law is contrary to the 1945 Constitution. However, with the use of âlegal logic of implication relationshipsâ in Constitutional Court Decision No. 110-111-112-113/PUU-VII/2009, the decision was made retroactive and it become the jurisprudence for the Constitutional Court Decision No. 5/PUU-IX/2011 and Decision No. 13/PUU-XI/2013.